Method for optimizing oxygen evolution reaction selectivity of FeCoOOH bimetallic oxyhydroxide catalytic material in seawater electrolysis based on first principle

Through first-principle calculation and single-atom metal doping technology, the structure of FeCoOOH bimetallic hydroxyoxide catalytic material is optimized, the corrosion problem caused by chloride ions in electrolytic seawater is solved, and the oxygen evolution reaction selection performance of catalytic material is improved.

CN119649933AInactive Publication Date: 2025-03-18SHENZHEN HINGEAR ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411724020.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the electrolytic seawater hydrogen production technology, the chloride ions in seawater will have a negative impact on the stability of the electrolyte and the activity of the catalyst, resulting in side reactions of chlorine and electrode corrosion problems.

Method used

The first-principle calculation method is used to predict the influence of surface doping groups on the adsorption properties of FeCoOOH bimetallic hydroxyoxides during the electrolysis process. Through single-atom metal doping (such as Ir doping), the structure of the catalytic material is optimized to avoid adsorption of chloride ions on the catalytic surface, thereby reducing corrosion.

Benefits of technology

Through doped atom site screening and electron density analysis, it is clear that chloride ions tend to hybridize with doped atoms rather than adsorb on the catalytic surface, effectively avoiding corrosion of catalytic materials and improving the oxygen evolution reaction selection performance of FeCoOOH bimetallic hydroxyoxide materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119649933A_ABST
    Figure CN119649933A_ABST
Patent Text Reader

Abstract

The invention discloses a method for optimizing oxygen evolution reaction selectivity of a FeCoOOH bimetallic oxyhydroxide catalytic material in seawater electrolysis based on a first principle. The method comprises the following steps: relaxation calculation based on the first principle, crystal face cutting of a FeCoOOH bimetallic oxyhydroxide material crystal, and calculation of system energy corresponding to a crystal stable configuration; establishing and constructing a stable adsorption configuration of chloride ions and hydroxyl with the target based on a first principle, performing relaxation calculation, and calculating corresponding system energy in an adsorption state; on the basis of the original stable configuration energy and the adsorption state stable configuration energy obtained in the early stage, the influence of different adsorption sites and different single atom doping on the adsorption performance of the chloride ion adsorption target is calculated. According to the method, the first principle is used for calculation, field experiments do not need to be carried out one by one for specific scenes, the adsorption performance changes of various monatomic groups in the process that the target chloride ions are adsorbed on the FeCoOOH bimetallic oxyhydroxide catalytic surface can be accurately estimated, and directional screening of catalytic monatomic on selectivity strategies is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new material technology, and more specifically to a method for optimizing the selective performance of FeCoOOH bimetallic oxyhydroxide catalytic material for oxygen evolution reaction in seawater electrolysis based on first principles. Background Art

[0002] In today's world, energy crisis and environmental pollution have become two major challenges facing the world. With the increasing depletion of fossil fuels and the damage to the environment caused by greenhouse gases produced by combustion, it is particularly important to find clean and sustainable energy solutions. Hydrogen energy, as an efficient and clean energy carrier, has great potential, and water electrolysis hydrogen production technology is one of the key ways to achieve the widespread application of hydrogen energy. Therefore, in-depth research on water electrolysis hydrogen production technology is of great significance.

[0003] The basic principle of water electrolysis hydrogen production technology is to decompose water into hydrogen and oxygen by electrolysis. This process is not only environmentally friendly, but also has abundant raw materials - water is almost everywhere on the earth. Compared with traditional fossil fuel hydrogen production methods, water electrolysis hydrogen production avoids greenhouse gas emissions, reduces environmental pollution, and is more in line with the requirements of sustainable development.

[0004] The necessity of studying water electrolysis hydrogen production technology is first reflected in the urgent need for energy transformation. With the growing global consensus on reducing carbon emissions and addressing climate change, governments are actively promoting the transformation of energy structure from dependence on fossil fuels to clean energy. As an important form of clean energy, the large-scale application of hydrogen energy will strongly promote this transformation process. As one of the core technologies for hydrogen energy production, the research and development of water electrolysis hydrogen production technology plays a vital role in achieving energy transformation.

[0005] However, since green hydrogen production requires pure water as a water source, the only freshwater resources that humans can actually use are a portion of rivers, lakes and groundwater, which only accounts for 0.26% of the total water on Earth. The large-scale demand for green hydrogen in the future world makes the bottleneck problem of water sources for hydrogen production particularly prominent. Therefore, it is necessary to break through the water source limitation of electrolytic hydrogen production and use more abundant salt water resources for green hydrogen production.

[0006] However, the technology of hydrogen production by electrolysis of seawater also faces some challenges. In particular, the chloride ions in seawater have a negative impact on the stability of the electrolyte and the activity of the catalyst. For example, the chloride ions in seawater will participate in the electrode reaction and lead to the production of chlorine or hypochlorous acid; the presence of chloride ions will corrode the electrode material and cause the electrode to deactivate and fall off; therefore, the problem of chlorine-oxygen side reaction and corrosion caused by the presence of chloride ions in salt water needs to be solved.

[0007] In order to solve the above problems, the present invention is proposed. Summary of the invention

[0008] The present invention aims to overcome the deficiencies of the prior art. The present invention discloses a method for predicting the influence of surface doping groups on the selective performance of chloride ion adsorption in the process of FeCoOOH bimetallic hydroxide water electrolysis based on first-principles calculation, and relates to the field of new material technology. The method includes: first-principles relaxation calculation, crystal face cutting of FeCoOOH bimetallic hydroxide material crystal, calculation of system energy corresponding to the stable configuration of the crystal; based on the first-principles construction, constructing the stable adsorption configuration of chloride ions and hydroxides with the target and performing relaxation calculation, and calculating the corresponding system energy in the adsorption state; based on the original stable configuration energy and the adsorption state stable configuration energy obtained in the early stage, calculating the influence of different adsorption sites and different single-atom doping on the adsorption performance of the chloride ion adsorption target, and analyzing according to the electronic state density and electronic differential charge. Using first-principles calculation, there is no need to carry out field experiments one by one for specific scenarios, and the adsorption performance changes of various single-atom groups in the process of FeCoOOH bimetallic hydroxide catalytic surface adsorption of target chloride ions can be accurately estimated, so as to realize the directional screening of catalytic single atoms for high selectivity strategies for oxygen evolution reaction.

[0009] The present invention adopts the following technical solutions:

[0010] The first aspect of the present invention is a method for optimizing the selectivity of FeCoOOH bimetallic oxyhydroxide catalytic materials for oxygen evolution reaction in seawater electrolysis based on first principles calculation (predicting the influence of surface doping groups on the chloride ion adsorption performance of FeCoOOH bimetallic oxyhydroxide in water electrolysis process based on first principles calculation, thereby improving the high selectivity of FeCoOOH bimetallic oxyhydroxide materials), comprising the following steps:

[0011] Step 1: Establish a supercell model of the FeCoOOH bimetallic oxyhydroxide material with high activity for catalytic oxygen evolution and establish a low-index crystal plane, and construct a supercell structure model based on the low-index crystal plane according to the actual preparation situation;

[0012] Step 2: Perform single-atom metal doping (iridium Ir) on the relaxed configuration, screen and calculate the doping sites and active catalytic atoms, and clarify the relaxed doping structure;

[0013] Step 3: Calculate the electronic state density and electronic differential charge for the doped relaxed structure to obtain initial steady-state data;

[0014] Step 4: Screen the adsorption sites of chloride ions and hydroxide ions of doping atoms to make sure that chloride ions and doping atoms are hybridized instead of being adsorbed on the surface of oxygen evolution materials;

[0015] Step 5: Perform calculation and analysis of the electronic state density and electronic differential charge of the relaxed chloride ion and hydroxide adsorption structures, compare the electronic structures of the chloride ion adsorption structure and the hydroxide adsorption structure, clarify that chloride ions are more inclined to dope atomic sites, avoid corrosion caused by the adsorption of chloride ions on the catalytic surface materials, and thus improve the selection performance of FeCoOOH bimetallic hydroxide materials.

[0016] By screening the sites where chloride ions are adsorbed on doped atoms, the protective effect of doped atoms on the surface of catalytic materials is analyzed;

[0017] By analyzing the effect of different metal doping on the adsorption and bonding of chloride ions through electronic localization functions, it is achieved that the electrode material can stably undergo oxygen evolution reaction in chloride ion solution, and the hybridization of chloride ions and catalytic materials will not lead to reconstruction of the active centers on the material surface.

[0018] Preferably, step one is specifically:

[0019] The calculation method is to set the plane wave function basis vector cutoff energy to 400eV, set the self-consistent iterative process optimization electronic wave function algorithm to Fast algorithm, and combine DAV and RMM algorithms. The self-consistent iterative cycle convergence standard is set to 1E-5eV, the maximum number of self-consistent iterative cycles is set to 150, the ion step relaxation algorithm selects the conjugate gradient method, and the ion step relaxation control is set to full relaxation, which is suitable for most three-dimensional structure optimizations. The overall calculation accuracy control is set to Normal, the electronic orbital fraction occupation broadening method is set to Gaussian method, and the broadening width is set to 0.2eV. Since Fe and Co are inherently magnetic, the electron spin polarized atomic magnetic moment is set to 5. Van der Waals force correction is added on the basis of DFT calculation. The van der Waals force calculation method is DFT-D3 method. The Hubbard U (DFT+U) treatment method is used for transition metals Fe and Co, and the U value of Fe is set to 5.3 and the U value of Co is set to 6.4.

[0020] The lattice and atomic positions of the FeCoOOH bimetallic oxyhydroxide unit cell were optimized. The lattice constants of the two-dimensional planar structure FeCoOOH after relaxation were a=8.78A and b=8.75A, and the angles between the lattices were all 90°.

[0021] Preferably, step 2 is specifically:

[0022] The initial charge density ρ0 is set, and the Ir metal element is selected to perform surface doping operation on FeCoOOH. The relaxed doping structure is determined by the Kohn-sham equation, which is as follows:

[0023]

[0024] First, based on the given initial charge density ρ0, the effective potential in the Kohn-Sham equation is determined. Subsequently, this equation is solved to obtain the single electron wave function, and the new charge density ρ is calculated using this wave function. Next, the difference between the newly calculated charge density ρ and the initial charge density ρ0 is compared. If the difference between the two is less than the preset convergence criterion, that is, the required accuracy requirement is met, the calculation process ends. On the contrary, if the convergence condition is not met, the new charge density ρ is mixed with the initial charge density ρ0 in a certain proportion to generate a new trial charge density, and the next iterative calculation is started. This iterative process will continue until the convergence criterion is reached, at which time the doping structure model reaches a stable state.

[0025] Preferably, step three is specifically as follows: reading the structural wave function data of FeCoOOH doped with Ir, calculating the electronic structure by increasing the Kohn-Sham orbital number to , and calculating the total density of states TDOS and the partial density of states PDOS respectively;

[0026] Preferably, step 4 is specifically: adding Cl ions to the Ir site of the doping structure, and adding Cl ions to the Fe and Co sites of the doping structure, and comparing the addition of Cl ions to the FeCoOOH crystal surface, respectively performing relaxation calculations, as shown in the attached manual. Figure 1 , Figure 2 shown.

[0027] Preferably, the chloride ion adsorption energy used in step 5 is determined based on:

[0028] E ads =E(IrFeCoOOH-Cl)-E(IrFeCoOOH)-E(Cl).

[0029] The hydroxyl adsorption energy used in step 5 is determined based on:

[0030] E ads =E(IrFeCoOOH-OH)-E(IrFeCoOOH)-E(OH).

[0031] Among them, E ads is the adsorption energy required for the adsorption state, E(IrFeCoOOH-Cl) is the total energy of chloride ions adsorbed on the Ir-doped FeCoOOH system, E(IrFeCoOOH-OH) is the total energy of hydroxide ions adsorbed on the Ir-doped FeCoOOH system, E(IrFeCoOOH) is the total energy of the doped FeCoOOH system, E(Cl) is the total energy of isolated Cl ions, and E(OH) is the total energy of isolated OH ions.

[0032] Preferably, step five is specifically as follows: read the wave function of Cl ion adsorbed on the Ir site on the surface of IrFeCoOOH, read the wave function of Cl ion adsorbed on the Co site on the surface of IrFeCoOOH, and read the wave function of Cl ion adsorbed on the Fe site on the surface of original FeCoOOH, and calculate the total density of states TDOS and partial wave density of states PDOS of each structure respectively. It can be seen from the results that Cl ions are more inclined to be adsorbed on Ir sites rather than Fe and Co sites in the doped structure. After manually adding Cl ions adsorbed on the Fe and Co sites of the doped structure and performing relaxation calculations, Cl ions will automatically adsorb near the Ir site, proving that the doping of Ir metal can replace the original Fe and Co sites. In addition, by comparing the density of states of the chloride ions adsorbed by the doped structure IrFeCoOOH and the original structure FeCoOOH, it can be proved that the Cl ions of the original structure produce hybridization peaks with Fe and Co near the Fermi level, and the bonding orbitals move toward the Fermi level, which proves that FeCoOOH is very susceptible to the corrosion of Cl ions during the electrolysis of salt water, and both Fe and Co sites are easily hybridized with Cl ions. In the doped system, due to the addition of Ir, the antibonding orbitals of Cl ions with Fe and Co move upward, and the Cl ions that originally hybridized with Fe and Co hybridize with Ir instead. The Ir atoms replace the original adsorption sites, avoiding the interaction between other metal element sites on the surface of IrFeCoOOH and Cl ions, thus avoiding the corrosion of the highly active FeCoOOH during the electrolysis of seawater. In addition, according to the adsorption energy calculation, E ads (Cl)=-4.90eV,E ads (OH) = -0.77 eV. The adsorption energy data also prove that Cl ions are more easily adsorbed on the doped Ir sites, and OH radicals will not be adsorbed on the Ir sites during the electrolysis of water, thus avoiding the impact on the catalytic activity during the electrolysis of IrFeCoOOH.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The present invention utilizes first-principles calculations, without the need to conduct field experiments one by one for specific scenarios, to accurately predict the changes in the adsorption performance of various single-atom groups during the adsorption of target chloride ions on the FeCoOOH bimetallic hydroxide catalytic surface, thereby achieving targeted screening of catalytic single atoms for high-performance strategies. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the structural diagram of FeCoOOH bimetallic hydroxide after doping Ir metal on the surface.

[0036] Figure 2After doping Ir metal on the surface of FeCoOOH bimetallic oxyhydroxide, it is calculated whether Cl ions will be adsorbed on the Fe and Co sites of FeCoOOH bimetallic oxyhydroxide and cause corrosion.

[0037] Figure 3 This is a comparison of the electronic state density diagram of chloride ions adsorbed after Ir doping and the original structure of FeCoOOH bimetallic hydroxide oxide adsorbing chloride ions. The left figure is the electronic state density of the doped state adsorbing chloride ions, and the right figure is the electrolytic state density diagram of the undoped original structure adsorbing chloride ions. DETAILED DESCRIPTION

[0038] The present invention is further described below by way of examples, which are not limited to the present examples. The experimental methods in the examples where specific conditions are not specified are generally carried out according to conventional conditions and conditions described in the manual, or according to the general equipment, materials, reagents, etc. used according to the conditions recommended by the manufacturer, which can be obtained from commercial channels unless otherwise specified. The technical scheme in the examples of the present invention will be described below in conjunction with the drawings in the examples of the present invention.

[0039] The present invention provides a method for optimizing the selectivity of FeCoOOH bimetallic oxyhydroxide catalytic material for oxygen evolution reaction in seawater electrolysis based on first principles, and the specific steps of the method are as follows:

[0040] Step 1: Establish a supercell model of the FeCoOOH bimetallic oxyhydroxide material with high activity for catalytic oxygen evolution and establish a low-index crystal plane, and construct a supercell structure model based on the low-index crystal plane according to the actual preparation situation;

[0041] Step 2: Perform single-atom metal doping (iridium Ir) on the relaxed configuration, screen and calculate the doping sites and active catalytic atoms, and clarify the relaxed doping structure;

[0042] Step 3: Calculate the electronic state density and electronic differential charge for the doped relaxed structure to obtain initial steady-state data;

[0043] Step 4: Screen the adsorption sites of chloride ions and hydroxide ions of doping atoms to make sure that chloride ions and doping atoms are hybridized instead of being adsorbed on the surface of oxygen evolution materials;

[0044] Step 5: Perform calculation and analysis of the electronic state density and electronic differential charge of the relaxed chloride ion and hydroxide adsorption structures, compare the electronic structures of the chloride ion adsorption structure and the hydroxide adsorption structure, clarify that chloride ions are more inclined to dope atomic sites, avoid corrosion caused by the adsorption of chloride ions on the catalytic surface materials, and thus improve the selection performance of FeCoOOH bimetallic hydroxide materials.

[0045] By screening the sites where chloride ions are adsorbed on doped atoms, the protective effect of doped atoms on the surface of catalytic materials is analyzed;

[0046] By analyzing the effect of different metal doping on the adsorption and bonding of chloride ions through electronic localization functions, it is achieved that the electrode material can stably undergo oxygen evolution reaction in chloride ion solution without causing reconstruction of the active centers on the material surface due to hybridization of chloride ions and catalytic materials.

[0047] Step 1 is as follows:

[0048] The calculation method is to set the plane wave function basis vector cutoff energy to 400eV, set the self-consistent iterative process optimization electronic wave function algorithm to Fast algorithm, and combine DAV and RMM algorithms. The self-consistent iterative cycle convergence standard is set to 1E-5eV, the maximum number of self-consistent iterative cycles is set to 150, the ion step relaxation algorithm selects the conjugate gradient method, and the ion step relaxation control is set to full relaxation, which is suitable for most three-dimensional structure optimizations. The overall calculation accuracy control is set to Normal, the electronic orbital fraction occupation broadening method is set to Gaussian method, and the broadening width is set to 0.2eV. Since Fe and Co are inherently magnetic, the electron spin polarized atomic magnetic moment is set to 5. Van der Waals force correction is added on the basis of DFT calculation. The van der Waals force calculation method is DFT-D3 method. The Hubbard U (DFT+U) treatment method is used for transition metals Fe and Co, and the U value of Fe is set to 5.3 and the U value of Co is set to 6.4.

[0049] The lattice and atomic positions of the FeCoOOH bimetallic oxyhydroxide unit cell were optimized. The lattice constants of the two-dimensional planar structure FeCoOOH after relaxation were a=8.78A and b=8.75A, and the angles between the lattices were all 90°.

[0050] Step 2 is as follows:

[0051] The initial charge density ρ0 is set, and the Ir metal element is selected to perform surface doping operation on FeCoOOH. The relaxed doping structure is determined by the Kohn-sham equation, which is as follows:

[0052]

[0053] First, based on the given initial charge density ρ0, the effective potential in the Kohn-Sham equation is determined. Subsequently, this equation is solved to obtain the single electron wave function, and the new charge density ρ is calculated using this wave function. Next, the difference between the newly calculated charge density ρ and the initial charge density ρ0 is compared. If the difference between the two is less than the preset convergence criterion, that is, the required accuracy requirement is met, the calculation process ends. On the contrary, if the convergence condition is not met, the new charge density ρ is mixed with the initial charge density ρ0 in a certain proportion to generate a new trial charge density, and the next iterative calculation is started. This iterative process will continue until the convergence criterion is reached, at which time the defect structure model reaches a stable state.

[0054] Step three is as follows: read the wave function data of the FeCoOOH structure doped with Ir, calculate the electronic structure by increasing the Kohn-Sham orbital number, and calculate the total density of states TDOS and the partial density of states PDOS respectively;

[0055] Step 4 is as follows: adding Cl ions to the Ir site of the doped structure, and adding Cl ions to the Fe and Co sites of the doped structure, and performing relaxation calculations on the FeCoOOH crystal surface, as shown in the attached manual. Figure 1 , Figure 2 shown.

[0056] The chloride ion adsorption energy used in step 5 is determined based on:

[0057] E ads =E(IrFeCoOOH-Cl)-E(IrFeCoOOH)-E(Cl).

[0058] The hydroxyl adsorption energy used in step 5 is determined based on:

[0059] E ads =E(IrFeCoOOH-OH)-E(IrFeCoOOH)-E(OH).

[0060] Among them, E ads is the adsorption energy required for the adsorption state, E(IrFeCoOOH-Cl) is the total energy of chloride ions adsorbed on the Ir-doped FeCoOOH system, E(IrFeCoOOH-OH) is the total energy of hydroxide ions adsorbed on the Ir-doped FeCoOOH system, E(IrFeCoOOH) is the total energy of the doped FeCoOOH system, E(Cl) is the total energy of isolated Cl ions, and E(OH) is the total energy of isolated OH ions.

[0061] Step 5 is specifically as follows: read the wave function of Cl ions adsorbed on the Ir site on the surface of IrFeCoOOH, read the wave function of Cl ions adsorbed on the Fe site on the surface of IrFeCoOOH, read the wave function of Cl ions adsorbed on the Co site on the surface of IrFeCoOOH, and read the wave function of Cl ions adsorbed on the Fe site on the surface of original FeCoOOH, and calculate the total density of states TDOS and partial wave density of states PDOS of each structure respectively. It can be seen from the results that Cl ions are more inclined to adsorb on Ir sites rather than Fe and Co sites in the doped structure. After manually adding Cl ions to adsorb on the Fe and Co sites of the doped structure and performing relaxation calculations, Cl ions will automatically adsorb near the Ir site, proving that the doping of Ir metal can replace the original Fe and Co sites. And comparing the density of states of chloride ions adsorbed on the doped structure IrFeCoOOH and the original structure FeCoOOH can also prove that the Cl ions in the original structure generate hybrid peaks with Fe and Co near the Fermi level, and the bonding orbitals move to the Fermi level, proving that FeCoOOH is very susceptible to the corrosion of Cl ions during the electrolysis of salt water, and both Fe and Co sites are easy to hybridize with Cl ions. In the doping system, due to the addition of Ir, the antibonding orbits of Cl ions and Fe and Co move upward, and the Cl ions that were originally hybridized with Fe and Co are hybridized with Ir instead. Ir atoms replace the original adsorption sites, avoiding the interaction between other metal element sites on the surface of IrFeCoOOH and Cl ions, thus avoiding the corrosion of highly active FeCoOOH during the electrolysis of seawater. In addition, according to the adsorption energy calculation, E ads (Cl)=-4.90eV,E ads (OH) = -0.77 eV. The adsorption energy data also prove that Cl ions are more easily adsorbed on the doped Ir sites, and OH radicals will not be adsorbed on the Ir sites during the electrolysis of water, thus avoiding the impact on the catalytic activity during the electrolysis of IrFeCoOOH.

[0062] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for optimizing the selectivity of FeCoOOH bimetallic oxyhydroxide catalytic materials for oxygen evolution reaction in seawater electrolysis based on first principles, characterized in that: The steps include: Step 1: Establish a supercell model of the FeCoOOH bimetallic oxyhydroxide material with high activity for catalytic oxygen evolution and establish a low-index crystal plane to construct a supercell structure model with a low-index crystal plane; Step 2: Doping the relaxed configuration with single-atom metal iridium Ir, and screening and calculating the doping sites and active catalytic atoms to clarify the relaxed doping structure; Step 3: Calculate the electronic state density and electronic differential charge for the doped relaxed structure to obtain initial steady-state data; Step 4: Screen the adsorption sites of chloride ions and hydroxide ions of doping atoms to make sure that chloride ions and doping atoms are hybridized instead of being adsorbed on the surface of oxygen evolution materials; Step 5: Perform calculation and analysis on the electronic state density and electronic differential charge of the relaxed chloride ion and hydroxide adsorption structures, compare the electronic structures of the chloride ion adsorption structure and the hydroxide adsorption structure, clarify that chloride ions are more inclined to dope atomic sites, avoid corrosion caused by the adsorption of chloride ions on the catalytic surface materials, and thus improve the selectivity of the FeCoOOH bimetallic hydroxide material for oxygen evolution reaction.

2. The method for optimizing the selectivity of FeCoOOH bimetallic oxyhydroxide catalytic material for oxygen evolution reaction in seawater electrolysis based on first principles according to claim 1, characterized in that: In step 1, the calculation method is to set the plane wave function basis vector cutoff energy to 400 eV, set the self-consistent iterative process to optimize the electron wave function algorithm to the Fast algorithm, and combine the DAV and RMM algorithms.

3. The method for optimizing the selectivity of FeCoOOH bimetallic oxyhydroxide catalytic material for oxygen evolution reaction in seawater electrolysis based on first principles according to claim 1, characterized in that: In step 2, the initial charge density ρ0 is set, the Ir metal element is selected to perform surface doping operation on FeCoOOH, and the relaxed doping structure is determined by the Kohn-sham equation. The calculation process is based on the Kohn-sham equation:

4. The method for optimizing the selectivity of FeCoOOH bimetallic oxyhydroxide catalytic material for oxygen evolution reaction in seawater electrolysis based on first principles according to claim 1, characterized in that: In step three, the structural wave function data of Ir-doped FeCoOOH is read, and the electronic structure is calculated by increasing the Kohn-Sham orbital number to calculate the total density of states TDOS and the partial density of states PDOS, respectively.

5. The method for optimizing the selectivity of FeCoOOH bimetallic oxyhydroxide catalytic material for oxygen evolution reaction in seawater electrolysis based on first principles according to claim 1, characterized in that: In step 4, Cl ions are added to the Ir site of the doped structure, and Cl ions are added to the Fe and Co sites of the doped structure, and relaxation calculations are performed respectively to compare the addition of Cl ions to the FeCoOOH crystal surface.

6. The method for optimizing the selectivity of FeCoOOH bimetallic oxyhydroxide catalytic material for oxygen evolution reaction in seawater electrolysis based on first principles according to claim 1, characterized in that: In step 5, the wave functions of Cl ions adsorbed on the Ir site on the IrFeCoOOH surface, the Fe site on the IrFeCoOOH surface, the Co site on the IrFeCoOOH surface, and the Fe site on the original FeCoOOH surface are read, and the total density of states TDOS and partial density of states PDOS of each structure are calculated respectively.

7. The method for optimizing the selectivity of FeCoOOH bimetallic oxyhydroxide catalytic material for oxygen evolution reaction in seawater electrolysis based on first principles according to claim 1, characterized in that: The chloride ion adsorption energy used in step 5 is determined based on: It is ads =E(IrFeCoOOH-Cl)-E(IrFeCoOOH)-E(Cl); The hydroxyl adsorption energy used in step 5 is determined based on: AND ads =E(IrFeCoOOH-OH)-E(IrFeCoOOH)-E(OH); Among them, E ads is the adsorption energy required for the adsorption state, E(IrFeCoOOH-Cl) is the total energy of chloride ions adsorbed on the Ir-doped FeCoOOH system, E(IrFeCoOOH-OH) is the total energy of hydroxide ions adsorbed on the Ir-doped FeCoOOH system, E(IrFeCoOOH) is the total energy of the doped FeCoOOH system, E(Cl) is the total energy of isolated Cl ions, and E(OH) is the total energy of isolated OH ions.